A systematic review on polyamines in human milk and infants formula milk - Mohamed, Siti Hajar; Abdul Ghani, Radiah (2018)
Introduction: Lacking of knowledge regarding infants’ care especially the importance of polyamines in human milk may lead to high choice in infant formula milk which lead to reducing of breastfeeding rate. A reduction in breastfeeding practice among mothers may one of the factors that lead to high mortality rate in infants. This worrying trend leads to urgency of obtaining the information on the role of polyamines in infants’ health and its level in human milk compared to formula milk. To date, there is no systematic review on the polyamines and its’ relation to infants’ health. Objective: This study aimed to identify the association between polyamines and health of the infants based on reviewed articles. Methods: Multiple databases were searched for English language studies of polyamines in milk and infant’s health. Studies in non-english language, articles published less than 2010 and not focused on polyamines in milk were excluded. Searches and identification of studies for inclusion were performed and the descriptive syntheses of finalized six papers were done. We reviewed six papers out of approximately 37 potentially relevant studies. Result and Discussion: All six papers are prospective cohort studies which done in several countries including Spain, Mediterranean area, Serbia and Sweden. Effect measures reported in these studies were consistent and suggested that polyamines are higher in human milk and have a positive impact on infant’s health. Conclusion: Overall, there is a moderate level of evidence supporting the hypothesis that polyamine in human milk is significantly higher compared with formula milk. However, there is a few high quality cohort studies exist recently which provide evidence the importance of polyamines in promoting proliferation of cells and accelerate the maturation of gut. Our finding warrants additional high quality research on this topic to be done especially in Asia region.